The role of IT capabilities, IT reconfiguration capability and innovativeness on organizational performance: evidence from the Brazilian public sector - Danilo Magno Marchiori; Ricardo Gouveia Rodrigues; Emerson Wagner Mainardes; Silvio Popadiuk (Revista de Administração Pública, 2023)
Abstract The growing investments in information technology (IT) each year pushes public sector organizations to develop the ability to gather, integrate, and implement these resources to improve organizational processes. Public sector organizations have to be agile and flexible to meet society’s dynamic demands. In this sense, IT management and creating an organizational environment facilitating innovation are crucial measures. These organizations must learn to cultivate IT capabilities and innovativeness to improve their performance and create public value. Thus, this study aims to identify the existing relationships between innovativeness, IT capabilities, IT reconfiguration capability, and organizational performance in the public sector. The research analyzed data from 254 Brazilian public organizations of the most diverse sizes and sectors using structural equation modeling (SEM). The results indicated that the ability to reconfigure IT must be listed among the organizations’ IT capabilities. Also, the findings suggest that IT capabilities foster organizations’ innovativeness, and IT capabilities and innovativeness positively impact the organizations’ performance. The study contributes to knowledge of innovation and IT capabilities by testing theoretical propositions identified in the context of the private sector but insufficiently assessed in the public sector. Finally, the study points out ways for public managers to better prepare their institutions to face constantly changing environments.